Strategi Pembelajaran Multikultural di Pendidikan Anak Usia Dini - Azizah Hanum; Sahrani Bibah; Bella Puspita Lubis (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Indonesia is a multicultural country with a diversity of ethnic groups, religions, cultures, languages, and customs; therefore, education that instills tolerance from an early age is essential. Multicultural education in Early Childhood Education (PAUD) is important to implement because early childhood is a stage of character formation and social-emotional development. This study aims to describe multicultural learning strategies in ECE, the principles of learning, the methods used, and their benefits for children’s development. The study employs a qualitative method using a literature review approach. Data were obtained from scientific journals, books, articles, and documents relevant to multicultural education for young children. Data analysis was conducted using a descriptive qualitative technique through data collection, reduction, presentation, and drawing of conclusions. The results of the study indicate that multicultural learning in early childhood education can be implemented through various methods such as storytelling, role-playing, regional songs, traditional games, and culture-based experiential learning. Such learning instills values of tolerance, empathy, justice, cooperation, and appreciation for diversity. Furthermore, multicultural education also provides benefits in the cognitive, affective, social, moral, and spiritual aspects of children.